If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5cx + y) = 34cx + -8y (5cx * 7 + y * 7) = 34cx + -8y (35cx + 7y) = 34cx + -8y Solving 35cx + 7y = 34cx + -8y Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-34cx' to each side of the equation. 35cx + -34cx + 7y = 34cx + -34cx + -8y Combine like terms: 35cx + -34cx = 1cx 1cx + 7y = 34cx + -34cx + -8y Combine like terms: 34cx + -34cx = 0 1cx + 7y = 0 + -8y 1cx + 7y = -8y Add '-7y' to each side of the equation. 1cx + 7y + -7y = -8y + -7y Combine like terms: 7y + -7y = 0 1cx + 0 = -8y + -7y 1cx = -8y + -7y Combine like terms: -8y + -7y = -15y 1cx = -15y Divide each side by '1x'. c = -15x-1y Simplifying c = -15x-1y
| 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) | | 5-2n=8n-(-4n) | | 5x-2x+21= | | (X)=(3x-10) | | X+X+25=75 | | 64=3x^2 | | 500x-0.69=700x+0.29 | | 8x/3-x=x/6-7/2 | | Y=4+3(-4) | | -6.4=128.0 | | 12x+2y=-48 | | 3.1x-37=2.1x+8 | | Y=-2+3(4) | | 1.8x+1-2.8x=4 | | Y=-2+3(3) | | (((2y^0)*(2xy^0))/(-xy^4))^-4 | | -3(3s-6)-18=-3(7s+3)-5 |